Sistema informático web para la gestión de la cartera de inversiones de la empresa Electro Oriente S.A., 2023 - Vargas Ipanama, Shiro (2024)
This research addresses the growing need for efficiency in project management within the electrical sector, driven by technological advancements, business expansion, and the demand for profitability. The study focuses on the challenges faced by electrical distribution companies in Peru in effectively managing their investment portfolios. Currently, these companies rely on limited tools such as Excel, which leads to manual errors, unreliable information, and inefficient project management. To tackle this issue, the development and implementation of a customized web-based information system is proposed. This system is designed to improve the time required for recording, tracking, and reporting investment plans, with the goal of optimizing the management of investment portfolios. The research follows a quantitative approach and adopts a pre-experimental design, including a comparative analysis before and after the system's implementation to assess its impact. The results show a significant improvement in operational efficiency, with a notable increase in the effectiveness of investment records, project tracking, and report generation. These findings confirm the hypothesis that implementing a web based information system optimizes investment management in the electrical sector. The conclusions emphasize the importance of adapting technological solutions to the specific needs of the electrical sector, recommending further customization of the system, integration with existing tools, and adequate staff training.